The Effectiveness of Video Tracker Use in STEM-Based Linear Motion Learning to Improve Students’ Critical Thinking Skills - anwar zaina; zakaria Al Farizi; Nurfadilah (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
Limited laboratory facilities and low levels of students’ critical thinking skills remain major challenges in physics learning, particularly on the topic of uniformly accelerated motion. This study aims to analyze the effectiveness of using Video Tracker media in STEM-based physics learning to improve students’ critical thinking skills. The research employed a quantitative method with a quasi-experimental design, namely the Nonequivalent Control Group Design. The subjects were students of class XI IPA as the experimental group and class X A as the control group at MA Muhammadiyah Nangahure. Research instruments included critical thinking skill tests, observations, and documentation. The results of the paired sample t-test indicated a significant difference between pretest and posttest scores in the experimental group (p < 0.05). Furthermore, the effect size value of 1.82 indicated a very large effect. These findings demonstrate that STEM-based learning integrated with Video Tracker is effective in enhancing students’ critical thinking skills and can serve as an alternative learning approach in schools with limited experimental facilities.